Managing the risk associated with income smoothening through social insurance in small states : some lessons from Trinidad and Tobago - Charles, Leslie ([Caribbean Centre for Money and Finance] [St. Augustine], 2005)
Reviews the literature on social security financing and the channels through which risks would impact on the ability of social insurance scheme to fulfill the promise of income smoothening through its pension system.